Tārikhī palṭanī : da maqālo majmūʻah - Muḥammad Hotak, fl. 1673-1730; Haywādmal, Zalmay (Da Puṣhto Ṭolanay da khparawano, 1977)
Critical evaluation of Patah Khazanah, biographies of early Pushto poets, by Muhammad Hotak, 18th century ; collections of articles.